Catch up : developing countries in the world economy - Nayyar, Deepak (Oxford : Oxford University Press, 2013)
This book is about the evolution of developing countries in the world economy situated in its wider historical context, spanning centuries, but with a focus on the period since the mid-twentieth century. It traces the rise and 'catch up' of the developing world and the shift in the balance of power in the world economy.
Prologue -- An untold story -- Part 1: Falling behind -- The great divergence and the great specialization -- Underlying questions and answers -- Part 2: Catching up -- End of divergence : beginnings of convergence? -- Engagement with the world economy -- Catch up in industrialization -- Unequal partners and uneven development -- Emerging divergences : inequality, exclusion, and poverty -- Epilogue -- The future in the past.
Includes bibliographical references (pages 192-211) and index.
Keywords: Economic development -- Developing countries -- History; Developing countries -- Foreign economic relations